The Inheritance Status of Test Tube Baby Children in the Perspective of Islamic Law and Inheritance Law in Indonesia - Annisa Fristyarini; Muhammad Yogi Galih Permana (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2023)
The issue of inheritance is a matter that is inherently related to human beings, as every individual will inevitably encounter the event of death. Inheritance law governs the rights and obligations concerning the transfer of inherited property to the surviving heirs after the deceased's death. Among the eligible heirs entitled to receive an inheritance from their parents are children, including those born through test tube baby procedures. This research aims to analyze the inheritance status of such children by Islamic law and inheritance law in Indonesia. This study employs a qualitative literature review methodology. The research findings indicate that in Islam, the inheritance rights of children born through the use of sperm and egg from a legitimate couple, where the embryo is transferred into the wife's womb, are considered equivalent to the rights of biological children. The child does not receive the inheritance if a third party is involved. Suppose the child is born out of wedlock (an illegitimate child). In that case, their share is attributed to the mother and her family. In Indonesia, there are three rules governing inheritance cases: customary inheritance law, determined by local customs; Islamic inheritance law, established by the Religious Courts; and civil law, which determines the inheritance share of legitimate children recognized by law. Meanwhile, children born out of wedlock only receive inheritance from the mother and her family.